Measurement of Wind Flow Behavior at the Leeward Side of Porous Fences Using Ultrasonic Anemometer Device. (January 2016) - Mustafa, Mohamad; Xu, Yizhong; Haritos, Geogre; Kenji, Kosugi
Abstract: Efficiency of wind fences is evaluated by the reduction of wind velocity and the effective shelter area behind the fence. Fence porosity is the most influential structural parameters in the porous fence design, and has significant impact on the structure of wind velocity and turbulence leeward. In this work, three fences with porosity of 23%, 35% and 45% have been tested under 10m/s inlet velocity in an environmental wind tunnel. An ultrasonic anemometer was used to measure three dimensional velocity vectors and the fluctuations of velocity vectors with a designed spatial resolution. The obtained data were used to calculate velocity magnitudes, turbulence intensities and turbulent kinetic energies in the test domain. Porosity influencing the structure of turbulence intensity and effective fence zone were discussed in this paper. Neither the distribution of wind velocities nor the structure of turbulence alone can provide sufficient information to assess the performance of porous fences. Consideration of the targeted reduction rate of wind velocity needs to be taken for optimal fence design.